E-Cigarettes and Young People: Communicating an Emerging Public Health Risk. Issue 6 (July 2019) - Mitchko, Jane; Lewis, Sarah; Marynak, Kristy L.; Shannon, Curt; Burnette, Deborah; King, Brian A.
E-cigarettes are the most commonly used tobacco product among US youth. Most e-cigarettes contain nicotine, which can cause addiction and can harm the developing adolescent brain. In coordination with the release of a Surgeon General's Report on e-cigarette use among young people, the Centers for Disease Control and Prevention collaborated with the Office of the Surgeon General to launch a campaign to educate parents, youth influencers, and young people about the risks of e-cigarettes. This article describes the development of communication products, including innovative media, about this public health risk, and shares lessons learned to inform public health practice.